Research handbook on small business social responsibility global perspectives - Laura J. Spence, Jedrzej George Frynas, Judy N. Muthuri, Jyoti Navare. (Editors) (Northampton, MA Edward Elgar Publishing, 2018)
ational context matters : influence of national business system on social enterprises in Scotland and India / Sreevas Sahasranamam and Christopher Ball -- Industry matters : comparative study of Vietnam's SME managers and workers on meaning and impacts of CSR in two manufacturing sectors / Angie Ngoc Tran and Sr̜en Jeppesen -- Cluster matters : corporate social responsibility and micro, small and medium-sized enterprise clusters in India / Mukesh Gulati, Peter Lund-Thomsen and Sangeetha Suresh -- Adding a small business perspective to research on working conditions in global production networks / Vivek Soundararajan -- SME resources and capabilities for sustainability performance : a framework for emerging economies / Burcin Hatipoglu -- Small business social responsibility and sustainability metrics : a focus on environmental performance measurement and waste / Diego Vazquez-Brust and Laura J. Spence -- Financial development and the efficiency of microfinance institutions / Niels Hermes, Robert Lensink and Aljar Meesters -- Corporate sustainability and social responsibility of smallholder farmers : implications for agriculture financing / Emmanuel Benjamin, Ebele Maduekwe, Maarten Punt and Gertrud Buchenrieder -- Financial aggregation of risks for MSMEs in developing economies : a conceptual framework of financial aggregation and microinsurance effects / Jyoti Navare and Morrison Handley-Schachler -- Exploring the global potential of social entrepreneurship and small business social responsibility for tackling societal value creation / Anica Zeyen and Markus Beckmann -- Social entrepreneurship and CSR theory : insights, application and value / David Littlewood and Diane Holt -- Hybrid organisations and models of social enterprise in Ghana and Bangladesh / Fergus Lyon and Abdullah Al Faruq -- The tree of knowledge : sustainable management practices for a collaborative ecosystem amongst small to medium enterprises / Heather Stewart and Rod Gapp -- Enabling sustainability in SMEs through action research / Patricia Hind and Arnold Smit -- Case study : scaling up social responsibility among small foundry clusters in India / Mukesh Gulati and Ruchita Sanwal -- Case study : clustering--a way to create shared value? a case study of a food and drink cluster organisation in England / Darla Dore -- Case study : human capital and environmental engagement of SMEs in Pakistan--a comparative analysis of the leather industry / Aqueel I. Wahga, Richard K. Blundel and Anja Schaefer -- Case Study : incubation and relevance of social businesses in rural Nepal : a case study of a social business incubator in Jumla / Ingeborg Patsch.
Includes bibliographical references and index.
Keywords: Social responsibility of business